Science assessment design based on environmental damage issues to strengthen students' literacy and numeracy competencies - Dhea Percatawati; Susi Rahmawati; Aprilia Rosida; Natsir Tamalene; Poppy Rahmatika Primandiri; Tutut Indah Sulistiyowati; Agus Muji Santoso (JPBIO (Jurnal Pendidikan Biologi), 2026)
Strengthening literacy and numeracy is a mandate of national education policy, as stipulated in Government Regulation No. 57 of 2021 and implemented through the Minimum Competency Assessment (AKM). However, science assessments in schools are still dominated by memorization-based questions that do not integrate real-world contexts and data representation. This study aims to develop and formatively validate a science assessment design for environmental change material based on Environmental Damage Issues to integrate literacy and numeracy contextually and ensure its feasibility and acceptability by junior high school students. The study used an educational design research approach with the Tessmer formative evaluation model. Data were collected through expert validation and student responses in one-to-one, small group, and field test stages, then analyzed descriptively and qualitatively. The results showed that 25 items were deemed feasible and acceptable. The integration of narrative text, graphs, tables, and diagrams encouraged data interpretation and contextual problem-solving.